Using Neuroimaging to Detect Covert Awareness and Determine Prognosis of Comatose Patients: Informing Surrogate Decision Makers of Individual Patient Results - Graham, Mackenzie; Doherty, Colin P.; Naci, Lorina (Seminars in Neurology, 2018)
Robust prognostic indicators of neurological recovery are urgently needed for acutely comatose patients. Functional neuroimaging is a highly sensitive tool for uncovering covert cognition and awareness in behaviorally nonresponsive patients with prolonged disorders of consciousness, and may be applicable to acutely comatose patients. Establishing a link between early detection of covert awareness in acutely comatose patients and eventual recovery of function could have significant implications for patient prognosis, treatment, and end-of-life decisions. Because functional neuroimaging of acutely comatose patients is currently limited to the research context, ethical guidelines for disseminating a patient's individual research results to clinical teams and surrogate decision makers are needed. We propose an ethical framework composed of four conditions that can guide ethical disclosure of individual results of neuroimaging research in the acute care context.
Keywords: neuroimaging; disorders of consciousness; brain injury; disclosure; research; ethics